The Effectiveness of Ground Transportation Modes on the Smooth Flow of Container Traffic in Cargo Shipments at PT Berkah Multi Cargo Logistics - Chuanda, Pricilia Anastasya (Universitas Diponegoro, 2024)
This research examines the influence of ground transportation modes on the smooth flow of container traffic at PT Berkah Multi Cargo Logistics. Utilizing both qualitative and quantitative methods, data was collected from various sources including literature reviews, interviews, and company records. The study identifies several factors contributing to the inefficiency of ground transportation modes, including inadequate fleet conditions, infrastructure limitations, and human resource constraints. Additionally, the research highlights the consequences of these inefficiencies, such as delayed deliveries leading to financial losses for cosignees, increased costs for consumers, and operational losses for the company. Despite efforts to adhere to company standards, the study suggests that improvements in ground transportation modes and infrastructure are necessary to enhance the efficiency of container traffic flow and mitigate associated challenges.